(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The dynamic responses of coastal areas to extreme events, including sea level rise. This will adversely impact the condition of coastal areas, such as Binuangeun Beach, which is currently experiencing abrasion due to being hit by big waves. This shows that the Lebak coastal area has the potential to experience vulnerability, especially due to sea level rise. The purpose of this study was to map the distribution of vulnerability of the coastal areas of Lebak Banten Regency to sea level rise. The method used in this study is the Coastal Vulnerability Index (CVI). The data collected consisted of primary data obtained by conducting field observations and secondary data obtained through NOAA, Copernicus, and IOC Sea Level Monitoring. Vulnerability variables analyzed were geomorphology, shoreline changes, elevation, sea level rise, tidal height, and wave height. The characteristic of the beaches of Lebak is coral, sand, and cliffs. The vulnerability assessment is divided into 3 classes, namely low, medium, and high. The research results show that the value Coastal Vulnerability Index (CVI) of the Lebak coast ranged from 2.9-2.19. Thus, all coastal sub-districts of Lebak Regency are included in the category of low vulnerability to sea level rise. This means that the Lebak coast is not potentially affected by disasters caused by sea level rise.